The preoperative plasma histamine level as a possible protective biomarker for postoperative acute kidney injury. Issue 1 (6th January 2023) - Guan, XinLiang; Li, Lei; Zhang, HongJia; Wang, XiaoLong
Abstract : Acute kidney injury (AKI) is a life-threatening complication of acute type A aortic dissection (ATAAD) patients. Increasing evidence suggests that histamine ameliorates the pathology of renal injury. However, data on the association between histamine levels and postoperative AKI in ATAAD patients are limited. The purpose of our study was to explore the incidence and independent risk factors of postoperative AKI, with special emphasis on the relationship between preoperative plasma histamine levels and the severity of postoperative ATAAD-AKI. This retrospective single-center study evaluated 160 patients with ATAAD admitted to the Beijing Anzhen Hospital aortic surgery database between April 2020 and December 2021. Univariate and multivariate logistic regression analyses were performed to determine the potential risk factors for postoperative ATAAD-AKI. A subgroup analysis was performed to investigate the association between preoperative plasma histamine levels and the severity of postoperative ATAAD-AKI or continuous renal replacement therapy (CRRT). ATAAD-AKI occurred in 84 of 160 patients (52.5%), including 32 with stage 1 (38.1%), 14 with stage 2 (16.7%), 38 with stage 3 (45.2%), and 34 (21.3%) received postoperative CRRT. The in-hospital mortality rate was 19.0% (16/84) in the AKI group and 2.6% (2/76) in the non-AKI group ( P = .02). Preoperative lower plasma histamine levels (odds ratio [OR], 1.31; 95% confidence interval [CI], 1.10–1.52; P = .004) were an important factor related to postoperative ATAAD-AKI in multivariate logistic regression analysis. Subgroup analysis revealed that low preoperative plasma histamine level was independently associated with postoperative ATAAD-AKI (stage 3) (OR, 1.38; 95% CI, 1.10–1.73; P = .005) and CRRT (OR, 1.44; 95% CI, 1.13–1.79; P = .008). Low preoperative plasma histamine level was an independent prognostic indicator of postoperative AKI in patients with ATAAD, especially for postoperative AKI (stage 3) and CRRT. Preoperative plasma histamine levels may serve as potential protective biomarkers of postoperative ATAAD-AKI.